Emergency endovascular management of gluteal artery pseudoaneurysm - Rohit Kumar Yadamreddy; M Lakshmidharan; Radhakrishnan Raju; M K Ayyappan (Indian Journal of Vascular and Endovascular Surgery, 2023)
Introduction: Gluteal artery pseudoaneurysms are rare, yet the most common in cases involving the superior gluteal artery. Pseudoaneurysms of the inferior gluteal artery are uncommon and are often related to blunt or penetrating trauma, infections and fractures of the pelvis. Presentation of Case: The authors describe a case of pseudoaneurysm which was presented to the emergency department. A thorough workup revealed a history of pelvic fracture that could constitute a probable cause of the pseudoaneurysm, which was treated with selective embolization of the artery during angiography. Discussion: The most common manifestation pseudoaneurysm of inferior gluteal artery is the presence of a painful mass in the buttock. However, both diagnosis and therapy are facilitated by catheter angiography. Conclusion: Although pseudoaneurysms are rare, pseudoaneurysms of the inferior gluteal artery require a high index of suspicion and careful physical examination by the physician in order to avoid misdiagnosis. In addition, the treatment performed using the endovascular technique is less invasive than the conventional technique, giving the patient better recovery.